IMMU-55. GD2 IS A MACROPHAGE CHECKPOINT MOLECULE AND COMBINED GD2/CD47 BLOCKADE RESULTS IN SYNERGISTIC EFFECTS AGAINST GD2 POSITIVE MALIGNANCIES. (9th November 2020) - Theruvath, Johanna; Mount, Christopher; Monje, Michelle; Mackall, Crystal; Majzner, Robbie
Abstract: GD2 is a disialoganglioside expressed on a variety of tumors including DIPG, neuroblastoma and osteosarcoma. Anti-GD2 antibodies have demonstrated some success in neuroblastoma and they have either not proven to be effective or have not been evaluated in other GD2 positive malignancies. CD47 is the dominant "Don't Eat Me" signal expressed by cancer cells to inhibit macrophages and blocking CD47 leads to phagocytosis of tumor cells. We hypothesized that CD47 blockade synergizes with anti-GD2. We measured in vitro phagocytosis of DIPG and NBL cells and observed a synergy of anti-GD2/CD47 compared to the single agents. In vivo, this combination led to the complete clearance of both orthotopic and metastatic models of NBL. Additionally, the combination significantly enhanced survival of OS xenografts. Finally, in a murine model of metastatic pulmonary OS, the combination led to a near elimination of all metastatic burden. To understand the underlying biologic basis, we studied the effects of GD2 crosslinking on tumor cells and the effects of GD2 blockade on macrophages. A portion of DIPG or NBL cells die when treated with dinutuximab, and those that survive upregulate surface calreticulin, an important pro-phagocytic ("Eat Me") signal. Additionally, we have identified the ligand for GD2, a molecule expressed on macrophages known to inhibit phagocytosis. In summary, we have identified a novel combination of anti-GD2 and anti-CD47 antibodies that is highly effective in preclinical models and will soon be tested in children. Furthermore, we have shown that GD2 itself is a macrophage checkpoint or "Don't Eat Me" signal.